The Politics of Risk and Young Offenders' Experiences of Social Exclusion and Restorative Justice - Gray, Patricia (The British journal of criminology, 2005)
The Crime and Disorder Act 1998 sets out a new framework for the governance of youth crime, with the primary aim of preventing criminality among young people by addressing the risk factors associated with offending. One of the main technologies of risk management is that of responsibilisation through restorative justice interventions. But the ethos of restorative justice envisages more than just holding young people responsible for their offending; it also professes a commitment to the restoration of victim-offender relations and the reintegration of young offenders into mainstream community life. However, in the prevailing penal climate, the principles of restorative justice have been narrowly interpreted to give undue weight to the responsibilisation of young offenders by challenging perceived deficits in their moral reasoning. The exclusionary socio-economic constraints that limit young offenders' choices and ability to reintegrate have been obscured. The end result is that restorative justice has become harnessed to the interests of reinforcing moral discipline' rather than engaging with social justice'. The argument is elaborated through the use of a recently completed research study conducted in the South-West of England, in which young offenders share, through in-depth interviews, their experiences of restorative justice and social exclusion